The relationship between and the characteristics of computing competence and confidence in undergraduate students of nursing - Todhunter, Carole Fern (2014)
The aim of this research was to understand the relationship between and the characteristics of computing competence and confidence in student nurses. The absence of a dominant paradigm for ICT, computers and computing influenced the choice of two sequential exploratory quantitative and explanatory qualitative studies. Data for the first study were collected through survey using a postal questionnaire, from a volunteer sample of student nurses. The results from a Principal Components Analysis influenced the second study. This was a recording of simultaneous concurrent think-aloud commentary and the behaviours of volunteer student nurses working in small groups on a computing activity. Protocol Analysis was used to examine a computing task outcomes and concurrent think-aloud comments. The results and findings showed a complex relationship between competence and confidence in this context. Students wanted a combination of teaching and social learning approaches. In both studies confidence had a high representation. This was evident where collaboration and social learning in small groups influenced confidence and competence. Research originality and its contribution to nursing lie first in the use of an innovative combination of methods. Secondly, the grouping and exploration of a range of subtle and seemingly unremarkable phenomena gave unique insight into how student nurses develop computing competence and confidence, not examined elsewhere. Both studies revealed differing levels of ability within and across the academic year groups. The findings show that attention to the social and psychological aspects of learning is crucial for skill and confidence development. Students would benefit from a bespoke range of approaches to suit their individual needs. This requires a balanced response between ongoing assessment of individual needs and proactive teaching and learning provision. Transferable to a wider setting, this research adds to the current understanding of ICT and computer related teaching and learning in nurse education.